2019
DOI: 10.1007/s13300-019-0674-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Sodium-Glucose Cotransporter 2 Inhibitors in East Asians with Type 2 Diabetes: A Systematic Review and Meta-Analysis

Abstract: IntroductionThe aim of this study was to assess the efficacy and safety of sodium-glucose cotransporter 2 (SGLT2) inhibitors in East Asians with type 2 diabetes mellitus (T2DM).MethodsA literature search that focused primarily on the PubMed, Embase, and Cochrane library databases was performed. All randomized controlled trials (RCTs) which satisfied the inclusion and exculsion criteria were eligible to be included in the meta-analysis. Risk ratios (RRs) and weighted mean differences (WMDs) were used as statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
36
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 57 publications
13
36
1
1
Order By: Relevance
“…A possible explanation for the lower incidence in E/SE Asians compared with non‐E/SE Asians may be that it is in part a result of cultural reporting bias, which was proposed as a possible explanation for similar findings in a study with canagliflozin in Asian patients with T2DM . A recent meta‐analysis of East Asian patients also reported a higher incidence of genital tract infections in those receiving SGLT2 inhibitors compared with the control treatment arms (placebo or non‐SGLT2 inhibitor antihyperglycaemic drugs) . Few patients in the E/SE Asian population had documented hypoglycaemia.…”
Section: Discussionmentioning
confidence: 94%
“…A possible explanation for the lower incidence in E/SE Asians compared with non‐E/SE Asians may be that it is in part a result of cultural reporting bias, which was proposed as a possible explanation for similar findings in a study with canagliflozin in Asian patients with T2DM . A recent meta‐analysis of East Asian patients also reported a higher incidence of genital tract infections in those receiving SGLT2 inhibitors compared with the control treatment arms (placebo or non‐SGLT2 inhibitor antihyperglycaemic drugs) . Few patients in the E/SE Asian population had documented hypoglycaemia.…”
Section: Discussionmentioning
confidence: 94%
“…In the meta-regression, the percentage of the population who were white and BMI at baseline were associated with HbA 1c reduction, whereas baseline HbA 1c was not correlated. A recent meta-analysis showed that efficacy and safety of SGLT-2i were favorable in East Asian patients with type 2 diabetes ( 13 ). It is interesting to know that SGLT-2i also show greater, albeit nonsignificant, cardiovascular risk reduction in Asians compared with other ethnic groups ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Where studies were conducted in relatively homogenous populations in Asian countries (e.g., Korea, China, Japan, and Taiwan), we have considered the participants to be in the "Asian" group. We have also followed the definitions of "East Asians" (China, Japan, Mongolia, North Korea, and South Korea) and "South Asians" (Afghanistan, Bangladesh, Bhutan, India, Maldives, Mauritius, Nepal, Pakistan, and Sri Lanka) from previous reports (13,14).…”
Section: Data Extractionmentioning
confidence: 99%
“…The rate of developing positive colonization and symptomatic vaginitis by the use of SGLT2 inhibitors in women who attended outpatient clinics in Japan appears to be higher in real‐world practice than in clinical trials. Meta‐analysis of the efficacy and safety profiles of SGLT2 inhibitors in East Asian patients with type 2 diabetes showed that the drugs significantly increased the risk of genital tract infection, but did not significantly increase the risk of hypoglycemia, urinary tract infection, hypotension or mortality.…”
Section: Major Benefits and Risks Of Sodium–glucose Cotransporter 2 Imentioning
confidence: 99%
“…The major benefits and risks of using SGLT2 inhibitors are listed in Table ; they should be carefully considered for appropriate use of the drugs. Reports regarding the clinical use of SGLT2 inhibitors are accumulating for both Asians and non‐Asians, and are expected to further clarify the risks and benefits of these drugs.…”
Section: Major Benefits and Risks Of Sodium–glucose Cotransporter 2 Imentioning
confidence: 99%